EPIDEMIOLOGICAL STUDIES ON EARLY BLIGHT DISEASE OF TOMATO - D. K. SAHU; C. P. KHARE; H. K. SINGH; R. PATEL; M. P. THAKUR (The Bioscan, 2014)
Alternaria leaf blight caused by Alternaria solani is a severe constraint in tomato production. The severity of this disease has been increasing day by day for last few years in India due to changes in environment. The field experiment was carried out to understand the development of early blight on tomato with respect to weather conditions during Rabi 2011-12 and 2012-13 at IGKV Raipur. Results showed that maximum temperature (r= -0.801 in 2011-12 and -0.564 in 2012-13), minimum temperature (r=-0.755 in 2011-12 and -0.682 in 2012- 13), relative humidity during morning (r=-0.550 in 2011-12 and -0.541 in 2012-13), relative humidity during evening (r=-0.593 in 2012-13) and rainfall (r=-0.531 in 2012-13) had strong negative and significant correlation with disease severity index (DSI) while relative humidity during evening (r=0.342 in 2011-12) and rainfall (r=0.409 in 2011-12) had positive correlation with DSI. Disease severity was found comparatively higher in the temperature range from 25.6-28.3°C (maximum) and 13.6-16.4°C (minimum) and average relative humidity 65% in the month of January 2011-12 and 2012-13.